2019
DOI: 10.1111/echo.14290
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of decreased left ventricular longitudinal deformation in asymptomatic patients with organic mitral regurgitation and preserved ejection fraction using tissue‐tracking mitral annular displacement by speckle‐tracking echocardiography

Abstract: Background Application of speckle‐tracking echocardiography (STE) provides rapid assessment of tissue‐tracking mitral annular displacement (TMAD). We investigated the value of TMAD for the assessment of decreased LV longitudinal deformation in asymptomatic patients with severe or moderate‐to‐severe mitral regurgitation (MR) and preserved LV ejection fraction (LVEF). Methods We retrospectively studied 50 patients with severe or moderate‐to‐severe organic MR and preserved LVEF (>60%) in whom global longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Thus, both GLS and GCS can re ect the recovery of left ventricular systolic function in patients with acute STEMI after PCI plus Tongxinluo treatment. GLS can more sensitively re ect changes in left ventricular systolic function than GCS and LVEF, which is consistent with the results of Teraguchi I, et al [20]. This may be because the inner myocardium is more sensitive to myocardial injury, it is located at the distal end of the coronary artery, with abundant microvessels and less effective collateral circulation, and the longitudinal myocardium is easily damaged after PCI [21].…”
Section: Discussionsupporting
confidence: 85%
“…Thus, both GLS and GCS can re ect the recovery of left ventricular systolic function in patients with acute STEMI after PCI plus Tongxinluo treatment. GLS can more sensitively re ect changes in left ventricular systolic function than GCS and LVEF, which is consistent with the results of Teraguchi I, et al [20]. This may be because the inner myocardium is more sensitive to myocardial injury, it is located at the distal end of the coronary artery, with abundant microvessels and less effective collateral circulation, and the longitudinal myocardium is easily damaged after PCI [21].…”
Section: Discussionsupporting
confidence: 85%
“…Not every parameter was reported on every patient's echocardiogram, hence the differing total numbers of patients for E/A and E/e' in our data. E/A and E/e' ratio can be abnormal when elevated or low [32]. In particular, E/A can be either increased or decreased depending on the type of diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…An association of TMAD with hard clinical outcomes, for which none of these studies was powered, was ambiguous . When the required times were measured, these were generally less than 15 seconds per echocardiographic view . Buss et al also examined lower‐quality images and found that in patients with reduced image quality (n = 67), TMAD acquisition could be performed more often than strain imaging (67 versus 43; P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…With speckle-tracking echocardiography (STE), software-based technology has emerged that quantifies myocardial deformation on the basis of 2D image loops. 31 In particular, speckle-tracking-based measurements of longitudinal LV [32][33][34][35][36][37][38][39][40][41] or even right ventricular (RV) 34,35,42 annular motion seem promising. However, many speckle-tracking-based measures require clear visualization of the endocardial border, and image quality is a main factor limiting their utility, particularly in point-of-care settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation